2023
DOI: 10.3390/horticulturae9040520
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Quality, Yield, and Soil Microecology of Ginseng in Different Planting Environments

Abstract: The quality and yield of ginseng are significantly affected by ecological factors, especially soil, which is a complex environment. This study compared the quality, yield, and soil differences of ginseng in a Mongolian oak forest (MOFG), birch forest (BFG), mixed wood forest (MWFG), poplar forest (PFG), farmland (FlG), and a felling forest (DfG). Based on these differences, the relationship between the three was explored, as was the most suitable forest type for developing understory ginseng cultivation. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
0
0
0
Order By: Relevance
“…In recent years, the understory planting system, as a novel plant method, has received much attention due to its various advantages. Lan et al [5] reported that cultivating forest-grown wild American ginseng can help reduce costs, increase market prices, improve ecological health, and maintain biodiversity. As a result, forest-grown wild American ginseng has gained widespread acceptance in different regions worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the understory planting system, as a novel plant method, has received much attention due to its various advantages. Lan et al [5] reported that cultivating forest-grown wild American ginseng can help reduce costs, increase market prices, improve ecological health, and maintain biodiversity. As a result, forest-grown wild American ginseng has gained widespread acceptance in different regions worldwide.…”
Section: Introductionmentioning
confidence: 99%